(untitled) (JÓVENES EN LA CIENCIA, 2024)
Price elasticity of demand (PED) is used to analyze in quantitative terms how the market of a given product adapts or adjusts to variations in the price of the same. The objective of this study was to estimate PED and its impacts on the variation of income (VI) of five traditional dairy products from Mexico, such as Oaxaca cheese (quesillo), Cotija cheese, goat curd (cuajada), cajeta (milk caramel) and chongos (sweet cheese). The data was obtained from the Foreign Agriculture Service (FAS), the United States Department of Agriculture (USDA) (1998-2018 period) through the tables provided and published on the Internet (secondary data). In this study, the arc method was applied to calculate PED and VI = ((Pf * Qf * 100) / (Pi * Qi)) - 100. The five products analyzed had a relatively elastic demand price in most of the years; on the contrary, the variation in income had positive and negative values, without a definite trend. It is concluded that there are no clear impacts of the PED on the sales revenue of the afore mentioned products; aspect that contradicts the theory of PED and its impact on income.